2003
DOI: 10.1016/s0736-5748(03)00087-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glial cell line‐derived neurotrophic factor (GDNF) co‐transplantation with fetal ventral mesencephalic cells (VMC) on functional restoration in 6‐hydroxydopamine (6‐OHDA) lesioned rat model of Parkinson's disease: neurobehavioral, neurochemical and immunohistochemical studies

Abstract: Among trophic factors already known, glial cell line-derived neurotrophic factor (GDNF) and other members of its family have potent and specific action on dopaminergic neurons. In the present investigation an attempt has been made to validate the role of GDNF co-transplantation with fetal ventral mesencephalic cells (VMC) on functional viability and restoration using neurobehavioral, neurochemical and immunohistochemical parameters at 6 weeks post-transplantation in 6-hydroxydopamine (6-OHDA) lesioned rat mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 45 publications
6
30
0
Order By: Relevance
“…It is well documented that GDNF can reduce dopaminergic neurons apoptosis, increase the survival and differentiation of fetal dopaminergic cell in vitro [17] . It has also been shown that GDNF can increase dopaminergic cell survival, graft-derived fiber outgrowth and overall functions of the graft after neural transplantation in rodent model of PD [18] . But the effect depends on the juncture and the dose of the GDNF addition.…”
Section: Trophic Factorsmentioning
confidence: 99%
“…It is well documented that GDNF can reduce dopaminergic neurons apoptosis, increase the survival and differentiation of fetal dopaminergic cell in vitro [17] . It has also been shown that GDNF can increase dopaminergic cell survival, graft-derived fiber outgrowth and overall functions of the graft after neural transplantation in rodent model of PD [18] . But the effect depends on the juncture and the dose of the GDNF addition.…”
Section: Trophic Factorsmentioning
confidence: 99%
“…DA and DOPAC levels in cultures were measured according to the modified method of Chaturvedi et al (2003). In brief, cultures were harvested by repeated pipetting and with the help of cell scraper.…”
Section: Vmc Culturementioning
confidence: 99%
“…Twelve weeks post transplantation six rats from each group (sham, lesioned, all transplanted groups) were assessed for circling behavior after injecting 5 mg/kg Damphetamine i.p following the method of Chaturvedi et al (2003). Rotational behavior was recorded after 30 min of injection, assessed for a period of 30 min and expressed as number of rotations/30 min.…”
Section: D-amphetamine Induced Circling Behaviormentioning
confidence: 99%
See 2 more Smart Citations